2007
DOI: 10.1149/1.2794462
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Whisker Formation in Tin-Based Solders Using Electrically Mediated Electrodeposition

Abstract: The global trend to eliminate lead from electronic devices is driven by legislative and marketing pressures based on environmental, health and social concerns on the cumulative effects of lead in waste streams. Tin and tin-rich alloys are the forerunning replacements for tin-lead solders.However, pure tin electrodeposits have a tendency to form tin whiskers that may cause short-circuiting, metal vapor arcing and failure of the component. The major cause of whisker growth is thought to be compressive stress in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The experimental results demonstrated that the increase in tin concentration in the electrolyte leads to an increase in the current efficiency of the electrolysis. The increase in the initial concentration of SnSO 4 ensures the availability of Sn 2+ ions on the interface of the cathode and electrolyte, thereby reducing the fraction of the electrical current used for hydrogen gas formation from the H + ions . The current efficiency is lower at the lower tin concentration because more electric current is consumed for the hydrogen gas evolution (i.e., 2H + + 2e = H 2 ).…”
Section: Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The experimental results demonstrated that the increase in tin concentration in the electrolyte leads to an increase in the current efficiency of the electrolysis. The increase in the initial concentration of SnSO 4 ensures the availability of Sn 2+ ions on the interface of the cathode and electrolyte, thereby reducing the fraction of the electrical current used for hydrogen gas formation from the H + ions . The current efficiency is lower at the lower tin concentration because more electric current is consumed for the hydrogen gas evolution (i.e., 2H + + 2e = H 2 ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…During the electrodeposition process to produce tin powder, thiourea will be adsorbed on the Sn nuclei and form a soluble complex species with Sn 2+ ions; thus, it will hinder the growth process and reduce the diffusion rate of an adatom on the cathode surface . The low diffusion rate of the adatom on the cathode surface leads to the formation of new nuclei, and the nucleation process is more dominant than the grain growth process . The limitation of the existing grain growth resulted in the tin powder having a smaller grain size.…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations